Sir Seth Thistlethwaite seeks the truth of Betty the Yeti - Thake, Richard, 1938- (Sir Seth Thistlethwaite ;, 2012)
"Who knows what is waiting to be discovered at the top of a mountain? Intrepid best buddies Sir Seth Thistlethwaite and Sir Ollie Everghettz find themselves stranded in Ah Ah Kaachu, an aloof alpine land with one big, bone-chilling problem. Betty the Yeti is threatening to bury the entire village of Nhu Kaachu under a hunormous avalanche! Do Sir Seth and Sir Ollie have what it takes to save this winter wonderland? Before they can, they'll need to face giant gelatinous beasts, a colossal killer 'pillar, and discover once and for all whether Betty is foe...or friend."--P. [4] of cover.